Laboratory accreditation and customer satisfaction - D Abhijith; K S Kusuma; M N Suma (Wolters Kluwer Medknow Publications, 2021)
Laboratory accreditation is a process by which an authoritative body gives formal recognition of technical competence for specific tests or measurements usually following international standards such as ISO/IEC 15189/17025. The process checks on inaccuracy or imprecision that may crop up during the preanalytical, analytical, or postanalytical phases, which could have an impact on the patient's reports and thereby the treatment aspects. The process itself helps the personnel of the laboratory to be alert, be quality conscious, and provide the best to the customers, namely patients and health-care providers, thereby helping the health-care providers to give the best of their services to the patients. This enhances the quality of the health-care services on the whole due to quality management system being in place in laboratories. The accreditation agency which takes interest in the laboratories of India and ensures quality in them is National Accreditation Board for Testing and Calibration Laboratories. The developed countries already have the system in place, and it is mandatory for every lab to be accredited before releasing patient reports. We are not far behind in this process, and shortly it may be considered to be mandatory for all labs to obtain the accreditation to run the tests. However, there are several challenges one needs to address in the process of accreditation, with the most important being the finances, team work, and planning.